Haemodynamic effects of acute beta-adrenergic receptor blockade in congestive cardiomyopathy. Issue 3 (September 1979) - Ikram, H; Chan, W; Bennett, S I; Bones, P J
Abstract : Acebutolol ('Sectral'), a cardioselective beta-blocking drug, was administered intravenously in a dose of 25 mg to 10 patients with congestive cardiomyopathy. All of them were in a stable condition on antifailure regimens. The drug resulted in a statistically significant decline in left ventricular contractility as judged by peak left ventricular dP/dT and the contractility index. The mean aortic blood pressure also fell. There was a significant increase in end-diastolic and end-systolic left ventricular volumes. Mean values for heart rate, ejection fraction, left ventricular stroke work index, and cardiac output also fell, but the results were not statistically significant. Left ventricular distensibility as judged by the slope of the diastolic pressure-volume relation also improved significantly. A reduction in myocardial energy requirements, improved compliance, and lowering of arterial pressure would be haemodynamically advantageous. However, further cardiac dilatation and reduction contractility--the basic defects in congestive cardiomyopathy--could lead to further deterioration.